The role of diet and food supplements in infertility management in the Eastern Mediterranean Region: A narrative review - Kassandra Said Fares; Georges Hani Abi Tayeh; Emile Roger Whaibeh; Romy Jihad Louis; Lina Yasser Jaalouk; Yara Matar Matar; Myriam Andraos Mrad (International Journal of Reproductive BioMedicine)
According to the World Health Organization, 17.5% of the population suffers from infertility. This demonstrates the critical need to expand access to high-quality reproductive care and increase our understanding of the factors that contribute to this issue. This review aims to summarize findings and gaps in the literature regarding diet-related factors and infertility among the Eastern Mediterranean couples poorly studied compared to other populations. The literature search was conducted using PubMed and Scopus databases from January 2012-July 2023. In total, 112 papers described the influence of diet and supplementation on natural and artificial reproductive outcomes in the Eastern Mediterranean Region and were found eligible for the review synthesis. For men, a diet rich in red meat, fatty foods, whole grains, and low in fish, poultry, low-fat dairy products, and vegetables have a positive effect on sperm count. For women, maintaining a healthy weight is crucial for their fertility. Overall, various vitamins and supplements significantly enhance gametes quality, hormonal balance, and antioxidant capacity, despite the results not being consistent across all studies. The findings highlight distinct dietary patterns that mitigate or exacerbate infertility risks, considering macro and micronutrients. Studies unevenly describe potential risk factors, underscoring the need for further exploration across diverse populations.